Possibilities for Engineered Insect Tissue as a Food Source - Rubio, Natalie R.; Fish, Kyle D.; Trimmer, Barry A.; Kaplan, David L. (Frontiers in Sustainable Food Systems, 2019)
Due to significant environmental concerns associated with industrial livestock farming, it is vital to accelerate the development of sustainable production methods for foods. Cellular agriculture presents an option, by using cell culture, as opposed to whole animals, to generate foods, including meats, eggs, and dairy products. The cost-effective scale-up of such cultured products requires addressing key constraints in core research areas: (1) cell sources, (2) growth media, (3) scaffolding biomaterials and (4) bioreactor design. Here we summarize work in the area of insect cell cultures as a promising avenue to address some of the needs in the field. Properties unique to invertebrate cells from insects allow for convenient and efficient tissue production and have already been exploited for various applications, such as industrial recombinant protein production. Insect muscle has also been employed in the field of tissue engineering for bioactuator applications. Compared to mammalian or avian cultures, invertebrate cell cultures require fewer resources and are more resilient to changes in environmental conditions, as they can thrive in a wide range of temperature, pH and osmolarity conditions. Alterations necessary for large-scale production are relatively simple to achieve with insect cells, including immortalization, serum-free media adaptation and suspension culture. Additional benefits include ease of transfection, nutrient density, and relevance to seafood organisms. To advance insect-based tissue engineering for food purposes, it is necessary to develop methods to regulate the differentiation of insect cells into relevant cell types, characterize cell interactions with biomaterials with an eye towards 3D culture, design supportive bioreactor systems and quantify nutritional profiles of cultured biomass.